Outcomes of switching to dasatinib after imatinib-related low-grade adverse events in patients with chronic myeloid leukemia in chronic phase: the DASPERSE study - Kim, Dong Wook; Saußele, Susanne (Annals of hematology, 2018)
Chronic, low-grade adverse events are common in patients with chronic myeloid leukemia who are treated with imatinib. These events may decrease patient quality of life and adherence, and may ultimately contribute to a suboptimal response. Alternative, second-generation tyrosine kinase inhibitors, such as dasatinib, are available with the potential to reduce adverse events, improve tolerability, and support long-term treatment goals. We present the final, primary analysis of DASPERSE/CA180-400 (NCT01660906), an open-label, multicenter, phase IV study designed to determine whether chronic, low-grade nonhematologic adverse events in imatinib-treated patients improve after switching to dasatinib, without affecting efficacy.
Gesehen am 18.10.2019